VIEWS OF SCIENTIFIC KNOWLEDGE OF EASTERN THINKERS - Muminova Dinara Shamilevna (Galaxy International Interdisciplinary Research Journal, 2022)
This article shows that the thinkers of the Renaissance, their scientific activity, the symbol of creativity and inventiveness in science are the power of inspiration and pride for scientists and researchers of our time. The wisdom of Eastern thinkers about science is attached. It was decided to study the universal and spiritual and moral principles mentioned in the "Holy Qur’an" and "Hadith Sharif"